TOURISM DEMAND AND EXOGENOUS EXCHANGE RATE IN CAMBODIA: A STOCHASTIC SEASONAL ARIMAX APPROACH - CHHORN, Theara (Theoretical and Practical Research in Economic Fields, 2018)
Time series seasonally displays toward either an autoregressive or moving average process where persist in seasonality fluctuation. The paper examines the relationship of tourism demand with controlling an exogenous exchange rate using seasonal ARIMA model. The empirical results reveal that HEGY test for seasonal unit roots with lower and upper panel indicates the statistical significance which explains the failure of rejection of having unit roots at different frequencies. The estimated outcomes from tourism demand model specify that per capita income and exchange rate have the power in explaining tourism demand measured as tourist arrivals. In particular to forecasting model and due to the lower statistical value of RMSE and MAE displays that the SARIMAX (4, 1, 1) – (1, 1, 1) 12 model is the best accuracy model to perform the long run ex-ante forecasting of tourism demand. This suggests tourism policy maker to pay more reflection in formulating the policy toward the exogenous factors in line with the uncertainty and unobserved seasonality.